(untitled) (XXI Century. Spanish Literature and Culture, 2024)
This article examines the resonances of Umberto Eco’s narrative and literary-theoretical work in Arturo Pérez-Reverte’s The Dumas Club. After highlighting the similarities between this novel and The Name of the Rose, we will explore how the theories of Lector in fabula and other theoretical texts by the Italian semiologist are reflected in The Dumas Club. In our view, one of the most interesting aspects of this novel is its use of fictional narrative to illustrate the fundamental issues of pragmatic-receptive literary criticism as defined by Umberto Eco: the role of the reader, cooperative interpretation and textual strategies.